Comparison of the Impact of Akmon, Sta-bar, Sta-pod, Stock cube, and Tribar Armoring Layers on the Level of Flow Rate and Wave Overtopping - Ali Safari; Mehdi Behdarvandi Askar (Journal of Hydraulic and Water Engineering)
Breakwaters are structures whose main function is to reduce waves in an area and create a calm basin for the stopping, movement, and maneuvering of floating objects. Concrete armors can be constructed in different shapes, allowing for the creation of armors that have high engagement properties and an increased damage coefficient (KD), ultimately leading to a reduction in the weight of armor pieces and their ability to be deployed in steeper slopes on the breakwater body. Most coastal protection structures built in the country are of the traditional rubble and platform type, and the structures made with concrete armor are few and far between. In this study, the impact of Akmon, Sta-bar, Sta-pod, Stock cube, and Tribar armoring layers on the level of flow rate and wave overwash in coastal protection structures and which type of armor has the least overflow is investigated. First, the overall geometry of the breakwater and then the geometry of each armor layer is separately drawn using AutoCAD software and prepared for calling to the main model, the FLOW-3D 11.0.4 software. After modeling, the results are analyzed through the main model and Excel software. The lowest wave overwash in the breakwater occurs in the Akmon armor state, and the highest wave overwash in the breakwater occurs in the Stock Cube armor layer state. The least flow rate among breakwaters occurred in the Akmon armor state, and the highest flow rate among the five breakwaters also occurred in the Stock Cube armor state, which is approximately.